PEMODELAN PERMINTAAN YANG MEMPERTIMBANGKAN HARGA, LOKASI DAN REBATE - Rizqa Amelia Zunaidi; Wahyu Andy Prastyabudi; Abduh Sayid Albana; Sinta Dewi; Nisrina Salsabilah (Spektrum Industri, 2019)
In accordance with Hottelling's Law, strategic location is a significant factor to ensure the success of a business, thus two businesses which sell the same product tend to choose a closed location. The real practice of this concept is seen in the competition of two big retailers which often open their shop nearby. However, in such competition, the location factor is merely not sufficient. It is necessary to consider other factors such as price and rebate or discount types given to their customers. This paper, particularly, aims to see the customers' preferences towards given attributes i.e. price, location, and discount types. The data is collected bymeans of a survey with non-probability sampling that is judgmental sampling. The respondents are people reside in Surabaya, Sidoarjo, and nearby whose age between 15-45 years and having various profession. The data is then processed with conjoint analysis by which is used as a basisto reconstruct a demand model considering the customer's preferences. The result shows that the attribute which is most considerable by respondents is the discount types, herein is a bundling product that comprises various products. This attribute has a preference level at 54.53%. The second prioritized attribute is the retailer location with a preference level at 24.28%. This means that a closer retailer is the most preferable by the respondent. Meanwhile, price is the last attribute considered by the respondent in choosing the retailer with a preference level at 21.28%. Thus, a respondent tends to pick a cheaper product after considering its discount type and the distance of retailer.